Cardiac looping may be driven by compressive loads resulting from unequal growth of the heart and pericardial cavity. Observations on a physical simulation model - Männer, Jörg; Bayraktar, Meric (Frontiers in Physiology, 2014)
The transformation of the straight embryonic heart tube into a helically wound loop is named cardiac looping. Such looping is regarded as an essential process in cardiac morphogenesis since it brings the building blocks of the developing heart into an approximation of their definitive topographical relationships. During the past two decades, a large number of genes have been identified which play important roles in cardiac looping. However, how genetic information is physically translated into the dynamic form changes of the looping heart is still poorly understood. The oldest hypothesis of cardiac looping mechanics attributes the form changes of the heart loop (ventral bending → simple helical coiling → complex helical coiling) to compressive loads resulting from growth differences between the heart and the pericardial cavity. In the present study, we have tested the physical plausibility of this hypothesis, which we call the growth-induced buckling hypothesis, for the first time. Using a physical simulation model, we show that growth-induced buckling of a straight elastic rod within the confined space of a hemispherical cavity can generate the same sequence of form changes as observed in the looping embryonic heart. Our simulation experiments have furthermore shown that, under bilaterally symmetric conditions, growth-induced buckling generates left- and right-handed helices (D-/L-loops) in a 1:1 ratio, while even subtle left- or rightward displacements of the caudal end of the elastic rod at the pre-buckling state are sufficient to direct the buckling process towards the generation of only D-loops or L-loops, respectively. Our data are discussed with respect to observations made in biological ‘models’. We conclude that compressive loads resulting from unequal growth of the heart and pericardial cavity play important roles in cardiac looping. Asymmetric positioning of the venous heart pole may direct these forces towards a biased generation of D- or L-loops.